Improving employee performance with technology acceptance model approach - Adyaksana, Rahandhika Ivan; Wicaksono, Crescentiano Agung; Ajiwinatama, Aychi Imelta (Journal of Business and Information Systems (e-ISSN: 2685-2543), 2024)
This research was conducted with the aim of determining the influence of task characteristics, technology characteristics, task-technology suitability, and use of technology on performance. The population used in this research are employees of the Yogyakarta Special Region Rural Credit Enterprise (BUKP) who are users of accounting information technology. The sample in this research was 71. This research used quantitative data with the data source used being primary data. The data collection technique used is data collection using a questionnaire. This research shows that task characteristics have a significant positive influence on technological task suitability, technological characteristics have a significant positive influence on technological task suitability, task and technology suitability have a significant positive influence on the use of information technology, task and technology suitability have a significant effect on performance impacts. , the use of technology has a significant effect on employee performance. This research is interesting because the objects in this research are rarely used.